2023
DOI: 10.1177/23779608231153473
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Hypertension Among Adults in Gurage Zone, Southwest Ethiopia, 2022

Abstract: Introduction Hypertension affects over a billion people worldwide, making it a major public health problem. The problem is significant in both developed and developing countries. However, studies are scarce in developing countries such as Ethiopia. Objectives This study aimed to assess the prevalence of hypertension and its associated factors at the community level, in South Ethiopia. Methods A cross-sectional study design was employed on a sample of 680 participants in the study from April 1 to June 30, 2022.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Weight and fat are the 2 nd and 3 rd leading drivers of HTN. This finding supports the conclusions of earlier investigations [ 62 ]. Excess body weight increases visceral and retroperitoneal fat, which can contribute to the development of HTN.…”
Section: Discussionsupporting
confidence: 94%
“…Weight and fat are the 2 nd and 3 rd leading drivers of HTN. This finding supports the conclusions of earlier investigations [ 62 ]. Excess body weight increases visceral and retroperitoneal fat, which can contribute to the development of HTN.…”
Section: Discussionsupporting
confidence: 94%
“…Media campaigns are used to expose large population to rising cases of stroke and other health-risk behaviours (Paiva et al, 2022). Hypertension affects over 1 billion people worldwide, making the disease a global health concern (Solomon et al, 2023). Too much dietary sodium is a contributory factor to cardiovascular disease, chronic disease and stroke.…”
Section: Discussion Tackling Issues Of Stroke and Hypertension Throug...mentioning
confidence: 99%
“… 19 , 25 , 26 In our study, individuals who reported using tobacco had almost 3 times higher odds of hypertension than nonusers, which is comparable to findings by Solomon et al who reported a fourfold increase in the risk of developing HTN among smokers compared to their counterparts. 27 Smoking causes an acute increase in blood pressure and heart rate and has been found to be associated with malignant HTN. Nicotine acts as an adrenergic agonist, mediating local and systemic catecholamine release and possibly the release of vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, individuals who reported a family history of HTN had almost 5-fold higher odds of HTN than those without, which is relatively similar to findings from a study in Southwest Ethiopia where a family history of HTN was associated with an approximately threefold increase in the risk of developing HTN. 27 Blood relatives tend to have many of the same genes that can predispose a person to HTN and share some habits, such as diet, exercise, and smoking, that can lead to high cholesterol, high body fat, and being more sensitive to the effects of salt on raising blood pressure. 29 This study has some limitations.…”
mentioning
confidence: 99%